Cross-examining the Role of the Directorate of Islamic Affairs, Nigerian Army in Eradicating Terrorism in the Northeast through the Counter-Narrative Programme - Uthman Okanlawon Sidiq; Abdul Gafar Olawale Fahm; Muhammad Bala Ahmad; Mustapha Adebayo Bello (Nur Science Institute, 2026)
Globally, kinetic approaches (military force) have been the primary tool in combating terrorism. Since the rise of the Islamic State West Africa Province (ISWAP), Jamāʿat Ahl al-Sunnah li-l-Daʿawah wa al-Jihād “Association of the People of the Sunnah for Preaching and Jihād” popularly known as Boko-Haram in 2009, the Nigerian military has heavily invested in weaponry. Still, it continues to suffer significant casualties despite some successes. This has led to the adoption of a non-kinetic approach known as Counter-Narrative Programme under the control of the Directorate of Islamic Affairs (DOIA), which has been battling the activities of these terrorists’ group. This might be the reason why the non-kinetic approach, termed the counter-narrative approach, was introduced. What is the counter-narrative program? What military operations are taking place in the country? Which directorate of the Nigerian Army is saddled with the program? What is the role of the Directorate of Islamic Affairs (DOIA)? How efficient is the counter-narrative program? What led to the abandonment of the programme? And what is the way forward for the government to avert the subsequent explosion of new terrorist groups like the recent Lakurawa in order not to turn to another gorilla war? This paper is both qualitative and historical in approach, in interrogating the aforementioned issues. The paper concluded by dichotomizing the significance of the programme from an Islamic perspective, discussing the shortcomings of the programme, and ends with achievable recommendations. REFERENCES Abdul-Azim, A.Z. (2000), Ṣaḥiḥ Muslim Arabic-English, Riyadh: Darussalam Agbiboa, D E. (2013), “No Retreat, No Surrender: Understanding the Religious Terrorism of Boko Haram in Nigeria.” Ajala, O. (2018), “Formation of Insurgent Groups: MEND and Boko Haram in Nigeria.” Small Wars & Insurgencies 29, no. 1, 112–130. Ajala O. (2025),